Private Higher Education in Africa: Old Realities and Emerging Trends - Tamrat, Wondwosen (International Journal of African Higher Education, 2018)
The growth of private higher education in Africa has been driven by factors such as burgeoning demand that could not be met by the public sector and policy inﬂuences as Structural Adjustment Programmes that promoted privatisation in the 1980s and beyond. In the past three decades, the continent’s private higher education institutions have exhibited diﬀerent growth trajectories. Variations are also evident in their policies and the quality of their oﬀerings. However, the variation and incremental growth of this sector is not adequately captured in the extant literature. This article investigates Africa’s private higher education sector based on past and emerging realities and argues that the sector exhibits nuances that have not received sufcient attention due to excessive stereotyping of PHE in Africa and elsewhere. Understanding these diﬀerences, which are sometimes described as ‘exceptions’, is a prerequisite for developing a comprehensive conceptualisation of current tapestries and future trends. The article begins by examining the major features of global private higher education and proceeds to Africa with its major focus on emerging trends within the continent. Des facteurs comme la demande croissante qui ne pouvait être absorbée par le secteur public et les inﬂuences politiques des Programmes d’Ajustement Structurel qui ont promu la privatisation pendant les années 80 et après sont à l’origine de la croissance de l’enseignement supérieur privé en Afrique. Pendant les trois dernières décennies, les institutions privées d’enseignement supérieur ont présenté diﬀérentes trajectoires de croissance. Des diﬀérences sont aussi observables quant à leurs politiques et à la qualité de leur oﬀre. Cependant, la variété et la croissance progressive de ce secteur ne sont pas correctement reﬂétées dans la littérature existante. Cet article examine le secteur de l’enseignement supérieur privé en Afrique à partir de réalités anciennes et nouvelles et soutient que les nuances de ce secteur n’ont pas reçu une attention sufsante à cause des stéréotypes excessifs auxquels fait face l’enseignement supérieur privé en Afrique et ailleurs. Comprendre ces diﬀérences, qui sont parfois catégorisées comme des exceptions, est un prérequis pour pouvoir conceptualiser de manière compréhensive le contexte actuel et les tendances futures. Cet article commence par analyser les caractéristiques principales de l’enseignement privé mondial avant de se focaliser sur l’Afrique avec une attention toute particulière pour les tendances émergentes sur le continent.